@Indigenousx: A Case Study of Community-Led Innovation in Digital Media. Issue 1 (November 2013) - Sweet, Melissa; Pearson, Luke; Dudgeon, Pat
The ever-increasing uses for social media and mobile technologies are bringing new opportunities for innovation and participation across societies, while challenging and disrupting the status quo. Characteristics of the digital age include the proliferation of user-driven innovation and the blurring of boundaries and roles, whether between the producers and users of news and other products or services, or between sectors. The @IndigenousX Twitter account, which has a different Aboriginal or Torres Strait Islander person tweeting each week, is an example of user-driven innovation and of how Indigenous voices are emerging strongly in the rapidly evolving digital landscape. Its founder, Luke Pearson, a teacher and Aboriginal education consultant, wanted to share the platform he had established on Twitter for storytelling to an engaged audience. The account can thus be seen as a form of citizen, participatory, community or alternative journalism. This article provides a preliminary analysis of @IndigenousX, and suggests that this account and the diversity of Indigenous voices in the digital environment offer opportunities for wide-ranging research endeavours. Initiatives like @IndigenousX are also a reminder that journalism has much to learn from innovation outside the conventional realm of journalistic practice.